Effectiveness of comparative advertising in eastern cultures. - Chong, Fui Khuen. (2008)
The paper examines whether the Asians and Westerners differ in their reactions to comparative advertising. The research was done using handphone as the research instrument. In the research a weak argument i.e. radiation is introduced against the strong arguments.